2002
DOI: 10.1046/j.1365-2591.2002.00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of smear layer removal by EDTAC and sodium hypochlorite with ultrasonic agitation

Abstract: Under ultrasonic agitation, sodium hypochlorite associated with EDTAC removed the smear layer from root canal walls, whereas irrigation with distilled water or 1.0% sodium hypochlorite alone did not remove smear layer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
108
2
45

Year Published

2008
2008
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(160 citation statements)
references
References 21 publications
5
108
2
45
Order By: Relevance
“…Baumgartner & Cuenin [37] also observed that ultrasonically energized NaOCl, even in higher concentrations such as 5.25%, did not remove smear layer from the root canal walls. Although the ability of PUI to remove the smear layer has been reported previously [38,25], our results showed that PUI was not superior to the XP-Endo finisher file under similar experimental conditions. This is in agreement with other studies [39,40], which have demonstrated that PUI did not completely remove smear layers from the apical third of canal walls.…”
Section: Jscholar Publisherscontrasting
confidence: 59%
“…Baumgartner & Cuenin [37] also observed that ultrasonically energized NaOCl, even in higher concentrations such as 5.25%, did not remove smear layer from the root canal walls. Although the ability of PUI to remove the smear layer has been reported previously [38,25], our results showed that PUI was not superior to the XP-Endo finisher file under similar experimental conditions. This is in agreement with other studies [39,40], which have demonstrated that PUI did not completely remove smear layers from the apical third of canal walls.…”
Section: Jscholar Publisherscontrasting
confidence: 59%
“…Guerisoli et al 57 (2002) propuseram a utilização do ultrassom para agitar as soluções e verificaram que a ação dos quelantes foi efetivada quando em maior contato com as superfícies dentinárias, através do carreamento do EDTA conduzido pelo ultrassom. O mesmo foi encontrado, em um estudo comparando a eficácia de diferentes soluções irrigadoras quando da irrigação clássica com seringa e irrigação passiva ultrassô-nica (PUI).…”
Section: Discussionunclassified
“…5 Removal of the smear layer can be considered an essential step in successful root canal treatment. 17 For this reason, the smear layer was removed in this study before evaluation of the penetration and adaptation of root canal filling materials. The quality of the filling depends largely on the sealing ability of the sealers.…”
Section: Stereomicroscopic Evaluationmentioning
confidence: 99%